Role of radiation therapy in primary tonsil large B cell lymphoma: a SEER-based analysis - Jia, Jing; Chen, Wenming (Radiation oncology (London, England), 2021)
Backgroud Primary tonsil diffuse large B cell lymphoma (PT-DLBCL) is an uncommon disease entity. The role of radiation therapy (RT) in PT-DLBCL is debatable in both the pre- and post- rituximab era. The purpose of this study was to evaluate the treatment outcome and establish a prognostic model in PT-DLBCL based on the Surveillance, Epidemiology, and End Results (SEER) database. Materials and methods Data of 1214 PT-DLBCL patients diagnosed between 1975 and 2016 were extracted from SEER 18. The effect of RT was assessed for the entire cohort and subgroups by stages using univariate, multivariate Cox regression analyses and propensity score matching (PSM). Results The entire cohort included 1043 patients with early-stage (ES) PT-DLBCL and 171 patients with advanced-stage (AS) disease. A decreasing trend of RT utilization in the ES cohort after 2002 was observed. 47.4% of patients in ES received RT, whereas 25.1% in AS underwent RT. RT significantly improved overall survival in both univariate ( P < 0.001) and multivariate ( P = 0.002) analyses. PSM analysis further validated the survival advantage of RT ( P = 0.002). A nomogram was established to predict the potential survival benefit. Subgroup analysis revealed RT was significantly associated with overall survival in ES patients of PT-DLBCL ( P = 0.001) and in the rituximab era ( P = 0.001) but not in those with AS disease ( P = 0.241). Conclusions This population-based study encloses the largest sample of PT-DLBCL to date and demonstrates a favorable survival role of RT in early stages rather than advanced stages. The established nomogram helps to identify high risk patients to improve prognosis.